NGHIÊN CỨU CÔNG NGHỆ CHẾ TẠO Co3O4 - ZrO2 KÍCH THƯỚC NANOMET - Trung, Nguyễn Quốc; Minh Nguyệt, Trần Thị; Thai, Nguyễn Doãn; Huấn, Nguyễn Quang; Chi, Trần Quế; Thư, Hà Phương; Chân, Đỗ Thế (Vietnam Journal of Chemistry, 2012)
Nano-material Co3O4-ZrO2 was preparated by Sol-Gel method with acid citric and polyethyleneglycol as ligands. Characterisations of the obtained oxides were studied by therma analysis (DTA, TGA, DTGA), X-ray diffraction (XRD) and Scanning Electron Microscopy (SEM). The resuls showed that by using of polyethyleneglycol as ligands we can fabricate Co3O4-ZrO2 with small particle size in the range 7 - 10 nm and by the citrat sol-gel method we obtained the sample with 20 - 25 nm particles.